Comprehensive physicochemical and photovoltaic analysis of different Zn substitutes (Mn, mg, Fe, Ni, Co, Ba, Sr) in CZTS-inspired thin film solar cells. Issue 16 (28th March 2022) - Lie, Stener; Guc, Maxim; Tunuguntla, Venkatesh; Izquierdo-Roca, Victor; Siebentritt, Susanne; Wong, Lydia Helena
Abstract : Comprehensive comparison among cations (X = Mn, Mg, Ni, Fe, Co, Ba, Sr) in Cu2 XSnS4 . Mn, Mg, Ba and Sr show photovoltaic responses, with Ba exhibiting the most potential. Abstract : The relatively stagnant efficiency of Cu2 ZnSnS4 (CZTS) kesterite thin film solar cells has led to the exploration of alternative materials based on the kesterite structure. The unavoidable formation of Cu–Zn disorder-related defects and Sn-related deep defects such as SnZn and its cluster in CZTS prompt various attempts to substitute Zn. However, the underlying principles behind the selection of the cation substitutes remain unclear since most studies have been performed using different synthetic strategies. In this study, CXTS (X = Zn, Mn, Mg, Ni, Fe, Co, Ba, Sr) thin films are synthesized by a facile spray pyrolysis and sulfurization method, and their physical properties and device performance are compared. It is found that a majority of the compounds form a tetragonal structure (kesterite or stannite); however, Mg + CTS and Ni + CTS are unstable in their quaternary structure and form a mixture of secondary phases, while CBaTS and CSrTS form trigonal structures. From UV-Vis spectroscopy, it is found that CMnTS, CBaTS and CSrTS exhibit steep and clear absorption edges, which make them promising solar cell absorbers. Meanwhile, high carrier concentrations (>10 18 cm −3 ) are observed for the compounds with transition metal substitutes (Mn, Mg, Ni, Fe, Co). Promising photovoltaic responses are observed in CMnTS, Mg + CTS, CBaTS and CSrTS, with CBaTS having the highest device performance possibly due to the lower band tailing, as observed from the photoluminescence and external quantum efficiency measurements. From these findings, correlations among the suitable cation substitutes for kesterite-inspired compounds are discussed and a guide for screening different cation substitutes for Zn in alternative I2 -II-IV-VI4 solar cells is provided.